The Diversity of South American Equus: Did Size Really Matter? - Machado, Helena; Avilla, Leonardo (Frontiers in Ecology and Evolution, 2019)
The Equus has a North American origin probably during the transition Miocene/Pliocene, and its entrance in South America is possibly related to one of the latest four events of the Great American Biotic Interchange. Nonetheless, the genus presented broad geographic distribution throughout South America. Traditionally, there were five species of Equus recognized to this continent and just recently they have been synonymized into three: Equus neogeus, E. insulatus and E. andium. However, their diagnoses are still unclear and a recent study showed that characters previously used are not taxonomically valid to distinguish such diversity, being inferred that in South America the genus was represented by a single species, E. neogeus. This contribution intends to update the knowledge of the diversity of South American Equus. In this sense, a synthesis of what is known so far as well as an update of the fossil record is presented here. Dental analyses were made and the results revealed a clear superimposition within the species. Also, autopodia characters were reanalyzed with greater sampling and the results once again corroborated that there was a single species presented in South America. The update of occurrences of the fossil record increased the knowledge of the geographical distribution of the genus in South America. There are records throughout almost all the continent, except for regions in the Amazon Forest, below latitude 40°, and altitudes above 3000m. Furthermore, its geographical distribution pattern along with the new incoming data revealed that E. neogeus fit as a smooth cline, in which the variation is gradual and continuous. It is also inferred that the phenotypic variation observed is probably related to the type of relief conformation.